Impact of Inflation, Interest Rates, And Money Supply on Deposit Funds - Yayan Luthfi Khoirina; Yuniar Farida; Moh. Hafiyusholeh; Hani Khaulasari (Economics Development Analysis Journal, 2024)
Deposits are straightforward investment instruments that offer fixed interest over a specified period, serving as a profitable product for banks. They play a crucial role in supporting banking operations, particularly within the internal scope of the institution. This study aims to examine the causal relationships between deposit interest rates, inflation, and money supply on the total deposits held by banks. A Vector Error Correction Model (VECM) is employed to investigate these relationships in both the short and long term. The analysis reveals that inflation and money supply significantly influence the volume of deposits in the short term. Conversely, deposit interest rates do not exhibit a substantial short-term impact on the total funds deposited. In the long term, all independent variables—deposit interest rates, inflation, and money supply—demonstrate a considerable effect on the amount of deposited funds. These findings provide valuable insights for banks, enabling them to optimize their funding strategies through deposit products while addressing challenges posed by macroeconomic fluctuations